Knowledge Management Practices of Universities in Bangladesh: Lecturers’ Perception - Kaniz Marium Akter; Subrata Banik (Universitas Syiah Kuala, 2019)
AbstractObjective – Aim of this study is to focus on the knowledge management practices of universities in Bangladesh. The study attempts to identify the level of four knowledge management dimensions that includes knowledge discovery, knowledge accumulation, knowledge sharing, and knowledge application. Design/methodology – A questionnaire survey was conducted to collect the primary data from 108 university lecturers in Bangladesh. The knowledge management practices of the universities in Bangladesh were recognized by utilizing a close-ended questionnaires that is adapted from the Becerra-Fernandez and Sabherwal’s Knowledge Management Process (2010). Results – Results indicated that three knowledge management dimensions are moderately practiced by the Bangladeshi universities. However, knowledge accumulation was the dominant dimension in comparison with others, where knowledge sharing was the least dominant dimension of knowledge management. Research limitations/implications – The study will facilitate the authorities of higher educational institutions to develop plans and strategies for practicing the knowledge management in the highest level. It is essential for creating a sound knowledge-based culture in the universities. Further research is recommended increasing the sample size and finding the impact of knowledge management on the organizational performance using SEM Model.